The Performance of an Integrated Transformer in a DC/DC Converter - Abdelhadi Namoune; Azzedine Hamid; Rachid Taleb (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The separation between the low-voltage part and high-voltage part of the converter is formed by a transformer that transfers power while jamming the DC ring. The resonant mode power oscillator is utilized to allow elevated competence power transfer. The on-chip transformer is probable to have elevated value inductance, elevated quality factors and elevated coupling coefficient to decrease the loss in the oscillation. The performance of a transformer is extremely dependent on the structure, topology and other essential structures that create it compatible with the integrated circuits IC process such as patterned ground shield (PGS). Different types of transformers are modeled and simulated in MATLAB; the performances are compared to select the optimum design. The on-chip transformer model is simulated and the Results of MATLAB simulation are exposed, showing an excellent agreement in radio frequency RF.